Evaluasi Kualitas Pelayanan dan Fasilitas Perpustakaan Terhadap Tingkat Kepuasan Mahasiswa Universitas Mahaputra Muhammad Yamin - Afni Yeni; Nurhayati; Diana Oktavia (Komunitas Dosen Indonesia, 2024)
The library functions as a multifaceted hub for knowledge acquisition, offering a range of services including access to library materials, reading assistance, educational support, information dissemination, foundational research activities, and various additional roles. Considering the previously discussed roles of the library, it is crucial for it to have superior facilities, deliver exceptional services, and improve the effectiveness of its librarians. This study aimed to assess how service quality and library facilities influence student satisfaction. This investigation utilizes a quantitative research approach. This study was carried out at the Campus I Library of Mahaputra Muhammad Yamin University. The subjects of this study consisted of all active students from Mahaputra Muhammad Yamin University who visited the library. The sampling method employed in this study was accidental sampling. This study involved a sample of 42 students. Data were collected through the distribution of questionnaires to participants. The findings of the study indicated that the quality of library services and facilities had a partial impact on student satisfaction. The quality of library services and facilities had a significant impact on student satisfaction.